Equal angles within a right triangle

Geometry Level 1

Given that E A D \triangle EAD has A = 9 0 \angle A=90^\circ , points B B and C C are on A D \overline{AD} such that A B = 1 AB=1 , B C = 2 BC=2 , C D = 3 CD=3 and A D E = B E C \angle ADE = \angle BEC .

Find x = A E x=AE .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let A D E = B E C = θ \angle ADE=\angle BEC = \theta . Then tan θ = tan A D E = x 6 sin θ = x x + 6 2 \tan \theta = \tan \angle ADE = \dfrac x6 \implies \sin \theta = \dfrac x{\sqrt{x+6^2}} . Since B E C \triangle BEC and E A D \triangle EAD has the same height x x , the ratio of their area is given by:

[ B E C ] [ E A D ] = B C A D = 2 6 = 1 3 3 [ B E C ] = [ E A D ] 3 × 1 2 × B E × C E × sin θ = 1 2 × A D × A E 3 × x 2 + 1 2 × x 2 + 3 2 × x x 2 + 6 2 = 6 x ( x 2 + 1 ) ( x 2 + 9 ) = 2 x 2 + 36 x 4 + 10 x 2 + 9 = 4 x 2 + 144 x 4 + 6 x 2 135 = 0 ( x 2 9 ) ( x 2 + 15 ) = 0 x 2 = 9 Since x 2 > 0 x = 3 \begin{aligned} \frac {[BEC]}{[EAD]} & = \frac {\overline{BC}}{\overline{AD}} = \frac 26 = \frac 13 \\ 3[BEC] & = [EAD] \\ 3 \times \frac 12 \times \overline{BE} \times \overline{CE} \times \sin \theta & = \frac 12 \times \overline{AD} \times \overline{AE} \\ 3 \times \sqrt{x^2+1^2} \times \sqrt{x^2+3^2} \times \frac x{\sqrt{x^2+6^2}} & = 6x \\ \sqrt{(x^2+1)(x^2+9)} & = 2 \sqrt{x^2+36} \\ x^4 + 10x^2 + 9 & = 4x^2 + 144 \\ x^4 + 6x^2 - 135 & = 0 \\ (x^2-9)(x^2+15) & = 0 \\ \implies x^2 & = 9 & \small \blue{\text{Since }x^2 > 0} \\ x & = \boxed 3 \end{aligned}

Let A E B = α \angle {AEB}=α and B E C = A D E = β \angle {BEC}=\angle {ADE}=β . Then tan α = 1 x \tan α=\dfrac{1}{x} , tan ( α + β ) = 3 x \tan (α+β)=\dfrac{3}{x} and tan β = x 6 \tan β=\dfrac{x}{6} . Using the identity tan ( α + β ) = tan α + tan β 1 tan α tan β \tan {(α+β)}= \dfrac{\tan α+\tan β}{1-\tan {α}\tan {β}} , we get x = 3 x=\boxed 3

Highly brillant , best approach to avoid lengthy equations .

Deep Rawat - 11 months, 2 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...